Profil Resiliensi Akademik Mahasiswa dan Kebutuhannya dalam Menghadapi Tantangan Tugas Akhir - Nuraini, Ni Luh Sakinah; Rini, Titis Angga; Cholifah, Puri Selfi; Aurelia, Davina; Wahyuni, Misye Agustin Tri; Afifah, Rifdah (Institut Agama Islam Negeri Kerinci, Indonesia, 2025)
Final-year students faced various challenges in completing their theses, which frequently causes anxiety and stress. This study aims to determine the level of resilience and encourage final year students in completing their thesis. The data collection technique in this study was a non-test in the form of a questionnaire with a resilience assessment scale with 106 higher education students as subjects. The results show that students with higher self-resilience tend to have good performance in problem solving. Mental health training as a treatment for students is an important means to complete a thesis with factors such as perfection, time management, motivation, and prioritization. This training also has a positive impact on students' thinking, encouraging a more positive mind-set, focusing on their goals to complete their final assignment, and helping students avoid things caused by procrastination. The recommendation from this research is the need for a structured mental health training program and increased support from lecturers and peers to help students face academic challenges.